SISTEM DETEKSI AIR TERKONTAMINASI LOGAM BESI (Fe) DENGAN PENGUKURAN INTENSITAS CAHAYA TERPOLARISASI - Agung Nugroho (Integrated Lab Journal, 2018)
Water is a necessity that important for human life, because water is needed for a variety of activities such as drinking, agriculture, industry and fisheries. Safe drinking water to health if it meets the requirements of physical, microbiological, chemical and radioactive. One chemical parameter requirements that must be met include ferrous metal content of at most 0.3 mg / l; In this study will focus on the content of iron (Fe) contained in the water or a solution by using the polarization of light. Integrated Laboratory UIN Sunan Kalijaga has polarized light intensity measuring equipment using a He-Ne laser beam. From the results of research samples with different concentrations showed maximum values of photo sensor readout element in polarization angle of -30 ° to -25 °. And maximum value of sensor readings in polarization angle of 45 ° - 80 °.